Cold and heavy: grasping the temperature–weight illusion - Kuhtz-Buschbeck, Johann P. (Exp Brain Res, 2020)
The apparent heaviness of weights placed on the skin depends on their temperature. We studied the effects of such a temperature–weight illusion (TWI) on perception and action in 21 healthy volunteers. Cold (18 °C), thermal-neutral (32 °C, skin temperature) and warm (41 °C) test objects were placed onto the palm of the non-dominant hand. Their veridical mass was 350 g (light) or 700 g (heavy). Perception of heaviness was assessed with two psychophysical experiments (magnitude estimation, cross modal matching). Cold heavy objects felt about 20% heavier than thermal-neutral objects of the same mass, shape and material. In a subsequent grip-lift experiment, the test objects were grasped with a precision grip of the dominant hand and lifted off the palm of the non-dominant hand. The grip and lift forces exerted by the fingertips were recorded. The temperature of the objects had significant effects (ANOVA, p < 0.05) on the peak grip and lift forces and on the peak grip force rate (i.e., the initial force incline). The peak grip force was about 10% higher when cold heavy objects were grasped and lifted, compared to lifts of otherwise identical thermal-neutral objects. The TWI was less pronounced when light objects or warm objects were handled. In conclusion, cooling of an object increases its apparent heaviness (perception) and influences scaling of the fingertip forces during grasping and lifting (action). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00221-020-05794-y) contains supplementary material, which is available to authorized users.